Nanoparticled Titanium Dioxide to Remediate Crude Oil Exposure. An In Vivo Approach in Dicentrarchus labrax - Patrizia Guidi; Margherita Bernardeschi; Vittoria Scarcelli; Paolo Lucchesi; Mara Palumbo; Ilaria Corsi; Giada Frenzilli (Toxics, 2022)
The contamination of marine water bodies with petroleum hydrocarbons represents a threat to ecosystems and human health. In addition to the surface slick of crude oil, the water-soluble fraction of petroleum is responsible for the induction of severe toxic effects at different cellular and molecular levels. Some petroleum-derived hydrocarbons are classified as carcinogenic and mutagenic contaminants; therefore, the oil spill into the marine environment can have long term consequences to the biota. Therefore, new tools able to remediate crude oil water accommodation fraction pollution in marine water are highly recommended. Nanomaterials were recently proposed in environmental remediation processes. In the present in vivo study, the efficacy of pure anatase titanium nanoparticles (n-TiO2) was tested on Dicentrarchus labrax exposed to the accommodated fraction of crude oil. It was found that n-TiO2 nano-powders themselves were harmless in terms of DNA primary damage, and the capability of pure anatase n-TiO2 to lower the levels of DNA damage induced by a mixture of genotoxic pollutant was revealed. These preliminary results on a laboratory scale are the prerequisite for deepening this new technology for the abatement of the cellular effects related with oil spill pollutants released in marine environments.